2006
DOI: 10.1038/sj.leu.2404495
|View full text |Cite
|
Sign up to set email alerts
|

Age and high-dose methotrexate are associated to clinical acute encephalopathy in FRALLE 93 trial for acute lymphoblastic leukemia in children

Abstract: The objective of the study was to assess acute neurotoxicity associated with triple intrathecal therapy (TIT)7high-dose methotrexate (HD MTX) in children with acute lymphoblastic leukemia (ALL). 1395 children were enrolled on FRALLE 93 protocol from 1993 to 1999. Lower-risk group (LR, n ¼ 182) were randomized to weekly low-dose MTX at 25 mg/m 2 /week (LD MTX, n ¼ 81) or HD MTX at 1.5 g/m 2 /2 weeks  6 (n ¼ 77). Intermediate-risk group (IR, n ¼ 672) were randomized to LD MTX (n ¼ 290) or HD MTX at 8 g/m 2 /2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 46 publications
(100 reference statements)
3
26
0
5
Order By: Relevance
“…The FRALLE 93 study population was stratified into three groups (low-risk, intermediate-risk, and high-risk) based on the following risk factors: age, whitecell count at diagnosis, hemoglobin level, immunophenotype, karyotype, and response to steroids. The treatment, which has already been published, 22 is described in the Online Supplementary Data.…”
Section: Design and Methodsmentioning
confidence: 99%
“…The FRALLE 93 study population was stratified into three groups (low-risk, intermediate-risk, and high-risk) based on the following risk factors: age, whitecell count at diagnosis, hemoglobin level, immunophenotype, karyotype, and response to steroids. The treatment, which has already been published, 22 is described in the Online Supplementary Data.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Winick et al [9] speculated that methotrexate was likely the causative agent, as the incidence dropped when patients were given folinic acid. Dufourg et al [6] found a significant increase of encephalopathy in patients treated with high-dose (10 of 20) versus lowdose (2 of 20) methotrexate (P = 0.03). They also found an increased incidence of encephalopathy and seizures in patients 10 years of age or older at onset of treatment.…”
Section: Methotrexatementioning
confidence: 97%
“…Dufourg et al [6] published a paper stating that patients treated with high-dose methotrexate were more likely to develop encephalopathy. Patients were treated with triple intrathecal therapy (methylprednisolone, methotrexate, and cytarabine) and either high-dose or low-dose methotrexate for ALL in the French FRALLE 93 trial.…”
Section: Methotrexatementioning
confidence: 99%
“…It can cause leukoencephalopathy, which ranges from acute and reversible to recurrent, chronic or irreversible and rarely fatal (5). The pathophysiology of leukoencephalopathy is not well understood.…”
Section: Introductionmentioning
confidence: 99%